Two new species of the Amphinemura sinensis group (Plecoptera: Nemouridae) from southern China - Mo, Raorao; Wang, Guoquan; Yang, Ding; Li, Weihai; Murányi, Dávid (Zootaxa, 2020)
Two new species of the genus Amphinemura in the sinensis species group, A. retusilobata sp. n. and A. simifleurdelia sp. n. are proposed from Guangdong Province and Guangxi Zhuang Autonomous Region of southern China, based on adults of both sexes. The new species are compared to related taxa and distribution map for the A. sinensis group is given.